2015
DOI: 10.17795/ajmb-25084
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Matrix Metalloproteinase-7 A-181G Polymorphism and the Risk of Relapsing-Remitting Multiple Sclerosis in Iranian Kurdish Patients from Kermanshah

Abstract: Background: Multiple sclerosis (MS) is a common chronic genetic disease of the central nervous system. The relapsing-remitting-MS (RR-MS) is the most common form of this disease. Matrix metalloproteinase-7 (MMP-7) is an important member of the MMP family, which degrades many extracellular matrix components. The common polymorphism of MMP-7 A-181G is associated with some diseases. Objectives: The aim of the present study was to determine the influence of this polymorphism on the risk of RR-MS. Materials and Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…in 2015, in which the frequency of the MMP-7 GG genotype was reported to be significantly higher in relapsing-remitting (RR) MS patients compared to that of healthy controls and concluded that the presence of this allele increases the risk of RRMS 1.58-fold. 13 A similar observation was reported in our study showing an association between the MMP-7 G allele and a 4.17-fold increase in risk for SLE. We did not find a significant association between the A/G + G/G genotype and autoantibody production except dsDNA autoantibodies ( p = 0.0312).…”
Section: Discussionsupporting
confidence: 90%
“…in 2015, in which the frequency of the MMP-7 GG genotype was reported to be significantly higher in relapsing-remitting (RR) MS patients compared to that of healthy controls and concluded that the presence of this allele increases the risk of RRMS 1.58-fold. 13 A similar observation was reported in our study showing an association between the MMP-7 G allele and a 4.17-fold increase in risk for SLE. We did not find a significant association between the A/G + G/G genotype and autoantibody production except dsDNA autoantibodies ( p = 0.0312).…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, MMP7 degrades soluble vascular endothelial growth factor receptor 1 (sVEGFR1) and increases the bioavailability of VEGF 165 , which promotes angiogenesis [42]. The G allele of the MMP7 -181 A/G SNP creates a putative binding site for a heat shock transcription factor, thereby increasing MMP7 gene promoter activity and transcription compared to the -181 A allele [34]. The G allele has been reported as a potential risk factor for several gynecological disorders, including endometriosis and adenomyosis [32], as well as endometrial [27], ovarian [26], and cervical cancers [28].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we extended this analysis to MMP7 and 12 genes, both of which exert important functions in pregnancy, including implantation and remodeling of spiral arteries. Additionally, polymorphisms in these genes have been investigated in different disorders, including gynecological [26][27][28] and non-gynecological cancers [29][30][31], as well as reproductive disorders [32,33] and various systemic disorders [34][35][36]. Our aim was to evaluate the potential association between IRSA in Slovenian reproductive couples and MMP7 -181 A/G and MMP12 -82 A/G functional SNPs, which are located in gene promoter regions.…”
Section: Introductionmentioning
confidence: 99%